2014
DOI: 10.1109/tec.2013.2292495
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Flywheel Energy Storage System for Power Smoothing in Wind Power Plants

Abstract: This work deals with the design and the experimental validation in scale-lab test benches of an energy management algorithm based on feedback control techniques for a flywheel energy storage device. The aim of the flywheel is to smooth the net power injected to the grid by a wind turbine or by a wind power plant. In particular, the objective is to compensate the power disturbances produced by the cycling torque disturbances of the wind turbines due to the airflow deviation through its tower section. The articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(58 citation statements)
references
References 27 publications
0
58
0
Order By: Relevance
“…The power interruptions due to cycling torque disturbance produced by wind turbines have been compensated by energy management algorithms depending on feedback control technologies [57]. Based on experimental findings, it was suggested that energy management algorithm can compensate the wind power fluctuations.…”
Section: Flywheel Energy Storage Systemmentioning
confidence: 99%
“…The power interruptions due to cycling torque disturbance produced by wind turbines have been compensated by energy management algorithms depending on feedback control technologies [57]. Based on experimental findings, it was suggested that energy management algorithm can compensate the wind power fluctuations.…”
Section: Flywheel Energy Storage Systemmentioning
confidence: 99%
“…Taking R(k + j|k) as the expected output at time k + j, the objective of MPC is to minimize the absolute error between the future output y(k + j|k) and the expected output R(k + j|k) , as shown in Equation (11).…”
Section: Traditional Lfamentioning
confidence: 99%
“…Power-smoothing schemes of WTGs can be divided into two groups: those with or without energy storage systems (ESSs) [8][9][10][11][12]. In [8][9][10], ESSs such as flywheels, supercapacitors, or batteries were suggested to smooth the frequency fluctuation caused by WTGs.…”
Section: Introductionmentioning
confidence: 99%
“…In [8][9][10], ESSs such as flywheels, supercapacitors, or batteries were suggested to smooth the frequency fluctuation caused by WTGs. ESSs help mitigate the frequency fluctuation by using their stored energy; however, these devices require an extra cost for installation and maintenance, particularly for a large-scale WTG.…”
Section: Introductionmentioning
confidence: 99%